Nilai-nilai karakter dalam makna moto hidup mahasiswa pendidikan bahasa dan sastra indonesia - Tri Mahajani (Universitas Sebelas Maret, 2020)
The research aims at describing character values incorporated in the embedded meaning of lives mottoes employed by the students of Bahasa Indonesia Education and Letters Study Program. This research applied qualitative approach and used content analysis method. The results show that there are exposed 1) character values that are related to the presence of God called religiosity, 2) character values that are placed on positioning oneself as indispensable; firstly hard-working that is grounded in respective human beings in building success, consistently in spreading the joy of kindness, hard-working in building prosperity; secondly responsible that is exposed as a means of living the life, being aware of life is encountered as teaching and learning media; thirdly independent which is represented in being capable of working without any helping from the others, succeed accomplished through the bitter of life paths, and becoming a kind person; 3) character values that are related to another human beings; firstly which is incorporating friendship and communication skills in a mutual friendship; as the key for maintaining kindness towards others, 4) character values that are related to the neighbourhood which is keeping the surrounding by loving it as the medium of livelihood understanding.